2020
DOI: 10.1111/1440-1630.12714
|View full text |Cite
|
Sign up to set email alerts
|

Participation patterns and determinants of participation of young children with cerebral palsy

Abstract: Introduction: Understanding participation patterns of young children with cerebral palsy (CP) will enable occupational therapists to tailor family-and child-centred services. This study compares participation patterns and participation barriers of young children with CP with those of typically developing (TD) children. In addition, effect of age and gender on participation were examined as well as child-related determinants of participation for young children with CP. Methods: Participants were a convenience s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Given that trunk control displayed a significant direct impact on dynamic balance, as evidenced by the path analysis in our structural equation model, it is understandable why children with hemiplegic CP performed better on functions related to trunk control. Furthermore, it’s important to note that manual ability plays a pivotal role in participation in daily activities (Abu-Dahab et al, 2021) and that children with diplegic CP had better manual ability outcomes in this study compared to those with hemiplegic CP. There was a substantial difference between the two groups in daily activities and social participation outcomes that favored children with hemiplegic CP.…”
Section: Discussionmentioning
confidence: 77%
“…Given that trunk control displayed a significant direct impact on dynamic balance, as evidenced by the path analysis in our structural equation model, it is understandable why children with hemiplegic CP performed better on functions related to trunk control. Furthermore, it’s important to note that manual ability plays a pivotal role in participation in daily activities (Abu-Dahab et al, 2021) and that children with diplegic CP had better manual ability outcomes in this study compared to those with hemiplegic CP. There was a substantial difference between the two groups in daily activities and social participation outcomes that favored children with hemiplegic CP.…”
Section: Discussionmentioning
confidence: 77%
“…Play activities, skill development, active physical recreation and social activities are the most common activities in which preschool children with CP participated [ 29 ]. Abu-Dahab et al determined that preschool children show low participation and activity levels for typically developing children [ 30 ]. Novak et al reported a relationship between goal-directed home program intervention and participation in children with CP aged between 2 and 7 years [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…In occupational therapy, multiple theoretical, practical, and institutional understandings of social participation are available, and there is a degree of consensus and some disagreements about its definition. For some authors, social participation includes social interactions, engagement in occupations/activities, and movement in places and spaces (Abu‐Dahab et al, 2021; Levasseur et al, 2019; P.B. Lopes & Matsukura, 2018; Veiguela et al, 2018).…”
Section: Introductionmentioning
confidence: 99%